Shooting to kill: the ethics of police and military use of lethal force - Miller, Seumas (Oxford University Press, 2016)
Terrorism, the use of military force in Afghanistan, Iraq, and Syria, and the fatal police shootings of unarmed persons have all contributed to renewed interest in the ethics of police and military use of lethal force. In this book the various moral justifications and responsibilities involved in the use of lethal force by police and military combatants are analyzed, relying on a distinctive normative teleological account of institutional roles. The resulting conception provides a novel theoretical alternative to prevailing reductive individualist and collectivist accounts. Police and military uses of lethal force are morally justified in part by recourse to fundamental natural moral rights and obligations, especially the right to personal self-defense and the moral obligation to defend the lives of innocent others. Yet the moral justification for police and military use of lethal force is to some extent role-specific. Police have an institutionally based moral duty to use lethal force to uphold the law, and military combatants have an institutionally based moral duty to use lethal force to win just wars. Two key notions in play are joint action and the natural right to self-defense. A relational individualist theory of joint actions is used to construct the notion of multilayered structures of joint action in order to explicate organizational action. A novel theory of justifiable killing in self-defense is also provided. Specific topics covered include: police shootings of armed offenders and suicide bombers; military necessity; targeted killing, autonomous weapons, humanitarian armed intervention, and civilian immunity.